Respon Berduka pada Pasien Kanker Payudara - Nia Kurniasih; Laili Rahayuwati; Lilis Mamuroh; Kusman Ibrahim; Raden Nabilah Putri Fauziyyah (State Islamic University of Sunan Ampel, 2022)
Cancer is one of the various non communicable diseases. Breast cancer often occurs at an advanced stage caused by a person's delay in early detection. Everyone has a different response in dealing with a disease. Grieving is an emotional reaction that a person feels towards loss. Several factors influencing the grieving response include age, stage, and duration of illness. This study aimed to identify the grieving response by age, stage of cancer, duration of illness, and determine the relationship between age, stage of cancer, duration of illness, and grieving response. The research method used descriptive correlational. The population in this study was 200 people with sampling technique using a total sampling of 200 respondents. Data analysis was univariate and bivariate using the Chi-Square correlation test. This research showed that almost all respondents were at the acceptance stage; nearly half were aged 45-54 years were in stage 3, and half had <1 year of illness. Correlation results showed a significant relationship between age and grieving response p-value 0.000 <0.050, but there was no significant relationship between stage, duration of illness, and grieving response p-value> 0.050. There is a relationship between age and grieving response. There is no relationship between cancer stage, duration of illness, and grieving response. This research can be used to develop information that age influences the grieving response in breast cancer patients.